Educational Inclusion in the Regular Classroom: an Asperger Syndrome Case - Andrade Ruiz, Fressy (2011)
The following paper resulted from the final research project conducted for my Master’s Degree in Teacher Training for Teachers of Primary Education (1st – 6th grade of the Basic General Education). This research project was conducted under the supervision of the Rural Education Division of the Center for Research and Teaching in Education (CIDE-UNA, Spanish acronym), in coordination with the Central America Educational and Cultural Coordination (CECC). The research is qualitative with an interpretative approach. Our main objective was to analyze the process of inclusive education in the regular classroom for a person with Asperger’s Syndrome, defined as a type of social impairment. The case study method was used in this research, as it allows a deeper study. A girl was chosen from a public school in an urban area of San José, Costa Rica. Three techniques were used to obtain information: interviews, questionnaires and documentation (personal file, behavior record, and psychological assessment) related to the girl with Asperger. The triangulation of sources was used as a method of analysis. The conclusion of the project was that regular schools may have children miss-diagnosed with Asperger’s Syndrome, and that our schools are still far from achieving inclusive education, but efforts are being made to achieve it. For a more opportune intervention, some recommendations based on this study were provided to the family and the school of the girl with Asperger.